A Multiscale Projection Method for Solving Nonlinear Integral Equations Under the Lipschitz Condition (Journal of Computational Mathematics, 2023)
We propose a multiscale projection method for the numerical solution of the irtativelyregularized Gauss-Newton method of nonlinear integral equations. An a posteriori rule issuggested to choose the stopping index of iteration and the rates of convergence are alsoderived under the Lipschitz condition. Numerical results are presented to demonstrate theefficiency and accuracy of the proposed method.